2022
DOI: 10.3389/fcvm.2022.839875
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Risk of Target Organ Damage in Different Phenotypes of Arterial Stiffness and Central Aortic Blood Pressure

Abstract: ObjectivesThe aim of this study was to explore the risk of target organ damage (TOD) in different groups based on carotid-femoral pulse wave velocity (cfPWV) and central aortic blood pressure (CBP) in different populations.MethodsThe study cohort was divided into four groups according to the status of cfPWV and CBP [Group (cfPWV/CBP): high cfPWV and high CBP; Group (cfPWV): high cfPWV and normal CBP; Group (CBP): normal cfPWV and high CBP; Group (control): normal cfPWV and normal CBP]. TOD was determined by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…After correcting for risk factors, we found that CDBP was independently associated with MAU in EHT. Other studies showed similar findings; for example, a cross-sectional study with 1,280 hypertensive patients found that CDBP greater than 90 mmHg was associated with MAU, changes in carotid artery intima-media thickness, and left ventricular hypertrophy [ 7 ]. However, some studies have also found that it is CPP that is a predictor of target organ damage.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…After correcting for risk factors, we found that CDBP was independently associated with MAU in EHT. Other studies showed similar findings; for example, a cross-sectional study with 1,280 hypertensive patients found that CDBP greater than 90 mmHg was associated with MAU, changes in carotid artery intima-media thickness, and left ventricular hypertrophy [ 7 ]. However, some studies have also found that it is CPP that is a predictor of target organ damage.…”
Section: Discussionmentioning
confidence: 60%
“…The same conclusion was reached in studies on children and adolescents [ 19 ]. In patients with risk factors for kidney injury, an increase in CSBP was found to increase the risk of developing MAU [ 7 ]. In our study, peripheral BP and CBP were correlated with log24 h-UAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary endpoint was to evaluate whether by using a therapeutic concordance approach a satisfactory BP control could be obtained in TRH patients. Secondary endpoints were: the percentage of hypertensive “difficult-to-control” patients (achieving BP control with the administration of more than three drugs [ 45 , 46 ]); the time course of target organ damage, defined by reduction in LVMha, carotid IMT, and GFR decline [ 47 ]; the incidence of major adverse CV events (MACE). The null hypothesis was rejected at a two-tailed p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…It has emerged as the gold standard method to measure arterial stiffness [2,3]. An elevation of CfPWV is an essential indicator for vessels and target organ damage [4].…”
Section: Introductionmentioning
confidence: 99%